2019
DOI: 10.3390/antiox8110518
|View full text |Cite
|
Sign up to set email alerts
|

A Role for H2O2 and TRPM2 in the Induction of Cell Death: Studies in KGN Cells

Abstract: Recent studies showed that KGN cells, derived from a human granulosa cell tumor (GCT), express NADPH oxidase 4 (NOX4), an important source of H2O2. Transient receptor potential melastatin 2 (TRPM2) channel is a Ca2+ permeable cation channel that can be activated by H2O2 and plays an important role in cellular functions. It is also able to promote susceptibility to cell death. We studied expression and functionality of TRPM2 in KGN cells and examined GCT tissue microarrays (TMAs) to explore in vivo relevance. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…TMAs were assembled from archived, no-longer-used residual paraffin material, as described earlier [ 28 ]. All the cases were pseudoanonymized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…TMAs were assembled from archived, no-longer-used residual paraffin material, as described earlier [ 28 ]. All the cases were pseudoanonymized.…”
Section: Methodsmentioning
confidence: 99%
“…The staining procedures were conducted as previously described [ 28 ]. The antibodies used for the study are listed in Supplementary Table S5 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms, by which cellular processes are changed in cancer, spread on different molecules (such as enzymes, transcription factors, or ion channels). An example of an ion channel is the transient receptor potential melastatin 2 (TRPM2), a Ca 2+ channel that can be activated by H 2 O 2 [14]. A study presented by Hack et al [14] showed parallel expression of NOX4 and TRPM2 in human granulosa cell tumor samples, suggesting that induction of oxidative stress could be beneficial for the therapy, as activation of this channel by H 2 O 2 increased Ca 2+ levels and apoptotic cell death.…”
mentioning
confidence: 99%